A horizon scan for improving pesticide management and governance in the great barrier reef catchment - Davis, Aaron M.; Attard, Steve; Di Bella, Lawrence; Shannon, Evan; Sluggett, Rob; Milla, Rob; Fillols, Emilie (Frontiers in Environmental Science, 2025)
The current policy environment for improving catchment pesticide water quality entering Australia’s Great Barrier Reef lagoon is based around Scientific Consensus Statement processes, which utilise systematic scientific literature reviews to develop policy recommendations. This paper modifies consensus approaches to incorporate structured horizon scanning into future policy needs facing farming sustainability in the Great Barrier Reef watershed. Horizon scanning identified several emerging challenges, and opportunities, spanning diverse themes including: a dynamic pesticide regulation and accessibility future; the need for better policy recognition of whole-of-farming system sustainability considerations; little consistency in integrated pest management frameworks across industries; technology; and increasingly complex stakeholder engagement needs. Several of the highest priority issues identified received no, or only cursory, attention in more backward-looking Scientific Consensus Statement outputs. These issues need careful integration into future Great Barrier Reef policy initiatives to maximise impact of already substantial government and industry investment in improved farming practice change.